Sistem Informasi Manajemen Pengajuan Surat Perintah Membayar (SPM) Berbasis Web Di Badan Pengelola Keuangan Dan Aset Daerah Kabupaten Hulu Sungai Tengah - Hafizah, Gina; Santosa, Tri Budi; Hasanah, Mahmudatun (Indonesian Journal of Information Technology and Computing (IMAGING), 2025)
The Regional Finance and Asset Management Agency (BPKAD) of Hulu Sungai Tengah Regency has an important role in managing regional finances effectively and efficiently. One of the main tasks of BPKAD Hulu Sungai Tengah Regency is to process the submission of a Payment Order (SPM) as the basis for disbursing budget funds. The SPM submission system at BPKAD Hulu Sungai Tengah Regency still does not work effectively and efficiently. Therefore, a web-based Payment Order Submission Management Information System (SPM) was designed to simplify the SPM submission process with the PHP programming language, MySQL as a database, and using the Bootstrap framework. This study uses the SDLC (System Development Life Cycle) method with the Waterfall model. The purpose of this system is to help and simplify the SPM application process at BPKAD Hulu Sungai Tengah Regency so that the SPM application process becomes more effective and efficient.